Markers of cholesterol synthesis are elevated in adolescents and young adults with type 2 diabetes. Issue 7 (15th September 2020) - Semova, Ivana; Levenson, Amy E.; Krawczyk, Joanna; Bullock, Kevin; Williams, Kathryn A.; Wadwa, R. Paul; Khoury, Philip R.; Kimball, Thomas R.; Urbina, Elaine M.; de Ferranti, Sarah D.; Maahs, David M.; Dolan, Lawrence M.; et al.
Abstract: Background: Changes in cholesterol absorption and cholesterol synthesis may promote dyslipidemia and cardiovascular disease in individuals with type 2 diabetes mellitus (T2DM). Objective: To assess cholesterol synthesis and absorption in lean individuals, obese individuals, and individuals with T2DM. Methods: We measured lathosterol and lanosterol (markers of cholesterol synthesis) as well as campesterol and β‐sitosterol (markers of cholesterol absorption) in the serum of 15 to 26 years old individuals with T2DM (n = 95), as well as their lean (n = 98) and obese (n = 92) controls. Results: Individuals with T2DM showed a 51% increase in lathosterol and a 65% increase in lanosterol compared to lean controls. Similarly, obese individuals showed a 31% increase in lathosterol compared to lean controls. Lathosterol and lanosterol were positively correlated with body mass index, fasting insulin and glucose, serum triglycerides, and C‐reactive protein, and negatively correlated with HDL‐cholesterol. In contrast, campesterol and β‐sitosterol were not altered in individuals with T2DM. Moreover, campesterol and β‐sitosterol were negatively correlated with body mass index, fasting insulin, and C‐reactive protein and were positively correlated with HDL‐cholesterol. Conclusions: Adolescents and young adults with T2DM show evidence of increased cholesterol synthesis compared to non‐diabetic lean controls. These findings suggest that T2DM may promote cardiovascular disease by increasing cholesterol synthesis, and provide additional rationale for the use of cholesterol synthesis inhibitors in this group.